Toya Gama installation as plain water source of UGM students - Migwa, Fathati Rizkiyani; Sofro, Zaenal Muttaqin; Penggalih, Mirza Hapsari Sakti Titis (BKM Public Health and Community Medicine, 2021)
Purpose: The installation of drinking water facilities in the school environment has been shown to increase students' water consumption. With the construction of the Toya Gama Drinking Water Supply System (SPAM Toya Gama) in 2014, the academic community at Universitas Gadjah Mada (UGM) gained improved access to clean drinking water, which is expected to impact overall health positively. This study aims to assess the effect of the SPAM Toya Gama installation as a drinking water source on the level of plain water consumption among UGM students in Yogyakarta. Methods: This was an observational study with a cross-sectional study design. The research was conducted on UGM undergraduate students in the 2018 class with a sample of 154 students taken by clustered sampling. Results: The average consumption of plain water was 1,665.76 ± 502.17 mL. Students who have used the SPAM Toya Gama facilities tend to have a higher level of plain water consumption, 14.9122 times that of those who have never used Toya Gama SPAM. The total liquid consumption also influences the level of plain water consumption. Conclusion: The average consumption of plain water was 1,665.76 ± 502.17 mL. The installation of SPAM Toya Gama affects the plain water consumption of UGM students. Their total fluid consumption also influences students' consumption of plain water.